Auditoría de gestión al sistema de comercialización y su incidencia en la rentabilidad de agro-servicio comercial “Arias”, cantón El Empalme, periodo 2012 - Aguirre Guerrero, Lisseth Monserrate (2015)
This research is the development in the company Agro-Commercial Service "ARIAS", located in the village of El Empalme at Av. Manabí km 1 1/2 Havoline sector, with the main objective to carry out a management audit system marketing and check its impact on profitability for the period 2012, the degree of compliance with the objectives and business goals are evaluated in order to assess the management and organizational development of the company, through the application of methods, types and research techniques as analytical, systematic, exploratory, descriptive, direct observation, and interview the Manager and Sub-Manager of the company. The Auditing is a process that involves fundamental aspects uses to detect deficiencies and irregularities that occur in the area audited, with the implementation of audit programs we sought to demonstrate the findings in the marketing system: the absence of a functional and procedural rules, lack of sales policies, lack of budget, lack of performance indicators, deficiency in the billing system, inadequate storage infrastructure and inadequate inventory management; however after having detected several shortcomings and have applied the internal control questionnaire was concluded that 40% of the functions are not made, the risk level is 25% demonstrates that there is deficiency, the confidence level of use of financial resources is 60% higher and control risk is 40% considered low and several shortcomings that does not meet the requirements are detected., that 15% risk control does not affect operations because their level 85 % considered high.